9. Transcranial direct current stimulation in prolonged disorders of consciousness - Estraneo, A.; Fiorenza, S.; Pascarella, A.; Moretta, P.; Masotta, O.; Loreto, V.; Trojano, L. (Clinical neurophysiology, 2017)
Transcranial direct current stimulation (tDCS) has been proposed as a novel non-invasive therapeutic approach in patients with disorders of consciousness (DOC), but its long-term effect has not been investigated yet. This randomized sham-controlled double-blind crossover study aimed at: (1) evaluating the long-term effects of five tDCS sessions on clinical and EEG findings in DOC patients; (2) identifying specific patients’ characteristics and EEG features in “responders” patients. Seven patients in vegetative state (VS) and 6 in minimally conscious state (MCS) at ⩾3months after brain-injury, were randomized into two groups who received: 1. One week of active tDCS and 1week of sham stimulation, separated by 1 resting week; 2. Reversed order of active and sham stimulation. Clinical and EEG evaluations were performed before and after the first stimulation session, two hours after 5 stimulation sessions and during a 3-month follow-up. Substantial clinical and EEG changes were observed in 3 patients in MCS and in 2 patients in VS starting 2–4weeks after active tDCS and further progressing during the next months. No baseline features distinguished “responders” from “non-responders”. tDCS might exert a long-term positive effect on clinical recovery in patients with prolonged DOC, and could represent a useful adjuvant strategy in neurorehabilitation.